Characterization of iron oxide nanoparticles by means of single-particle ICP-mass spectrometry (SP-ICP-MS) – chemical versus physical resolution to overcome spectral overlap. Issue 9 (6th August 2020) - Rua-Ibarz, Ana; Bolea-Fernandez, Eduardo; Pozo, Guillermo; Dominguez-Benetton, Xochitl; Vanhaecke, Frank; Tirez, Kristof
Abstract : In this work, different single-particle ICP-MS (SP-ICP-MS) approaches, relying on either chemical or physical resolution to overcome spectral overlap, have been assessed for their utility in the characterization of iron oxide nanoparticles (IONPs). Abstract : As a result of their unique physical, chemical and/or biological properties, the use of engineered nanoparticles (ENPs) is growing very rapidly. Iron oxide nanoparticles (IONPs) are of particular interest owing to their magnetic properties, and thus the development of suitable methods for their characterization is essential. Inductively coupled plasma-mass spectrometry (ICP-MS) operated in single-particle (SP) mode provides different types of relevant information, such as size distribution and particle number and mass concentrations. However, the use of SP-ICP-MS becomes less straightforward when the analyte signal is subject to spectral overlap. In the case of IONPs, characterization by means of SP-ICP-MS is hindered by the occurrence of ArO + polyatomic ions with the same nominal mass-to-charge ( m / z ) ratio as the most abundant Fe isotope. In this work, different approaches relying on either chemical or physical (mass) resolution, to avoid this spectral interference otherwise jeopardizing accurate results, were assessed. In the case of chemical resolution, the performance of on-mass and mass-shift approaches was evaluated using different types of quadrupole-based ICP-MS instrumentation, including single-quadrupole (SQ) and tandem ICP-MS (ICP-MS/MS) units. Physical resolution was accomplished using a new generation of sector field (SF) ICP-MS instrumentation, capable of dealing with transient signals of extremely short duration (10–100 μs dwell time), even when operated at higher mass resolution (pseudo-resolution mode). Based on the figures-of-merit obtained for the different approaches evaluated, an on-mass approach using NH3 as the reaction gas in SQ-ICP-MS, an on-mass approach using H2 as the collision/reaction gas in ICP-MS/MS and pseudo-medium resolution in SF-ICP-MS were found to be the best-suited approaches for fast interference-free monitoring of the ion signals generated by IONPs in SP mode. While the use of chemical (H2 /on-mass) and physical (pseudo-medium) resolutions also provided accurate and precise results for custom-made Fe3 O4 (magnetite) NPs of ≈50 nm, the use of NH3 was less successful, as it leads to an extension of the SP pulse profile and a lower signal-to-background ratio. Finally, SF-ICP-MS operated in pseudo-medium resolution mode was used for the characterization of Fe3 O4 NPs synthesized electrochemically (batch and continuous operation mode).